Influence of Karl Marx's Political Thought in 20th Century - Sanjeev Anand; Mukesh Kumar Mishra (ZBW - Leibniz Information Centre for Economics, 2020)
The task of this paper discusses the role of Marx in 20th Century and culture today. An analysis of contemporary political economy Studies works that with the new global crisis of capitalism, a new interest in Karl Marx's works has emerged. Karl Marx—German philosopher, economist, and revolutionary—believed a just world could be achieved only through the evolution of humanity from a capitalist to a socialist economy and society. The new world economic crisis that started is the most obvious reason for the return of the interest in Marx. The paper argues that Marx's Both a scholar and a political activist, Marx addressed a wide range of political as well as social issues, and is known for, among other things, his analysis of history. The interpretations of his theories, particularly those on political economy, have in the course of history generated decades of debate, inspired revolutions and cast him as both devil and deity in political and academic circles.
Keywords: 330; Karl Marx; Marxist theory; Global Economy